Substance use among inmates at the Eldoret prison in Western Kenya - Kinyanjui, Daniel WC (BioMed Central, 2013)
BACKGROUND: Criminal activity and social problems are recognized as important outcomes of substance use and abuse. Little research has been carried out on substance use among prison inmates in Kenya. General population surveys that have examined drug use usually omit this ‘hidden’ population which may offer insight into drug related morbidity and invaluable preventive measures. This study is set out to determine the lifetime prevalence and factors associated with substance use, including the most frequently used substances, among inmates at a government prison in Western Kenya. METHODS: Design: A cross-sectional descriptive study, using the WHO model questionnaire and an additional drug use and effects questionnaire among prisoners at the Eldoret Government of Kenya (GK) prison, Kenya. Setting: Study was carried out at the Eldoret G.K. prison, with a population of 1325 (1200 males and 125 females) inmates. Subjects: Three hundred and ninety five prisoners, who gave consent, were selected, consisting of 271 males (68.6%) selected by simple random sampling, and 124 females (31.4%) enrolled consecutively due to their small number. The mean age was 33.3 years (18–72, s.d. 9.8) while the mean number of years of formal education was 8.4 (0–15, s.d. 3.4). RESULTS: Lifetime prevalence of substance use was 66.1%, while that of alcohol use was 65.1%. Both were significantly associated with male gender, urban residence and higher level of education. The lifetime prevalence of cigarette use was 32.7% while 22.5% admitted to chewing tobacco. Factors significantly associated with tobacco use were male gender, urban residence, being unmarried, younger age, lack of income in the past year. The prevalence of cannabis use was 21%, and this was associated with male gender, urban residence, being unmarried, and being a student in the past year. Other substances used included amphetamines (9.4%), volatile inhalants (9.1%), sedatives (3.8%), tranquillizers (2.3%), cocaine (2.3%), and heroine (1.3%). Users were commonly introduced to the habit by friends (70.8%), immediate family members (13.7%) and other close relatives (6.2%). Among those who reported lifetime substance use the common reasons attributed to the habit were the need to relax (26.5%), relieve stress (24.5%) and confidence to commit a crime (4.5%). Majority of those who reported alcohol use were already suffering ill effects. CONCLUSIONS: There is a high prevalence of substance use among prisoners at the Eldoret G.K. prison. The increased morbidity and unpleasant psychosocial consequences of this habit suggest a need for establishment of substance use management programmes in Kenyan prisons.